2022
DOI: 10.3389/fphar.2022.943538
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide microRNA profiles identify miR-107 as a top miRNA associating with expression of the CYP3As and other drug metabolizing cytochrome P450 enzymes in the liver

Abstract: Cytochrome P450 (CYP) drug metabolizing enzymes are responsible for the metabolism of over 70% of currently used medications with the CYP3A family being the most important CYP enzymes in the liver. Large inter-person variability in expression/activity of the CYP3As greatly affects drug exposure and treatment outcomes, yet the cause of such variability remains elusive. Micro-RNAs (miRNAs) are small noncoding RNAs that negatively regulate gene expression and are involved in diverse cellular processes including m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 67 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…The further construction of the lncRNA/circRNA-miRNA-mRNA-pathway regulation network showed that miR-1260 and miR-107_R-2 were involved in the regulation of the glycerolipid metabolism pathway. It was found that miR-1260 and miR-107 were closely related to the expression of cytochrome P450 (CYP) enzymes, including CYP3A4, CYP3A5, and CYP3A43 [51]. MiR-107 is highly expressed in the skeletal muscle of Qinchuan cattle, and circFGFR4 can promote myoblast differentiation by binding with miR-107 [52].…”
Section: Discussionmentioning
confidence: 99%
“…The further construction of the lncRNA/circRNA-miRNA-mRNA-pathway regulation network showed that miR-1260 and miR-107_R-2 were involved in the regulation of the glycerolipid metabolism pathway. It was found that miR-1260 and miR-107 were closely related to the expression of cytochrome P450 (CYP) enzymes, including CYP3A4, CYP3A5, and CYP3A43 [51]. MiR-107 is highly expressed in the skeletal muscle of Qinchuan cattle, and circFGFR4 can promote myoblast differentiation by binding with miR-107 [52].…”
Section: Discussionmentioning
confidence: 99%
“…The interrelated roles of miRNA, lncRNA, and genetic polymorphisms in regulating PXR expression are reviewed extensively by Smutny et al (2021 ). A recent ex vivo study by Tantawy et al found significant associations between miR-107 and nine different transcription factors that regulate expression of CYP3A enzymes; the transcription factors include estrogen receptor alpha ( ESR1 ), PXR, hepatocyte nuclear factor 3-beta ( FOXA2 ), HNF4A , and peroxisome proliferator activated receptor alpha ( PPARA ) ( Tantawy et al, 2022 ). These results suggest that miR-107 does not directly regulate CYP3A expression by binding to mRNA for CYP3As; rather, miR-107 may modulate the expression of multiple key transcription factors affecting P450 expression ( Tantawy et al, 2022 ).…”
Section: Circulating Ncrnasmentioning
confidence: 99%
“…A recent ex vivo study by Tantawy et al found significant associations between miR-107 and nine different transcription factors that regulate expression of CYP3A enzymes; the transcription factors include estrogen receptor alpha ( ESR1 ), PXR, hepatocyte nuclear factor 3-beta ( FOXA2 ), HNF4A , and peroxisome proliferator activated receptor alpha ( PPARA ) ( Tantawy et al, 2022 ). These results suggest that miR-107 does not directly regulate CYP3A expression by binding to mRNA for CYP3As; rather, miR-107 may modulate the expression of multiple key transcription factors affecting P450 expression ( Tantawy et al, 2022 ). As liquid biopsy analysis of cfRNA in exosomes continues to gain interest, it is important to note that a mechanism for the association between circulating exosomal miRNA and the metabolic clearance rates of DME substrates remains largely unknown ( Pridgeon et al, 2022 ).…”
Section: Circulating Ncrnasmentioning
confidence: 99%
“…Differences in drug metabolism between males and females often lead to distinct AEs due to higher expression and activity of CYP3A enzyme for females than males [14]. Midazolam is a widely used hypnotic metabolized by CYP3A in the liver, and pharmacokinetic differences between males and females have been reported [15].…”
Section: Real Data Analysismentioning
confidence: 99%